Smart Car Parking System - Sumathi A,; Lakshmi Bhaskar,; Prateeksha K Ankolekar,; Shreya Shenoy,; Vaishnavi Bhatt, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In this fast-growing economy, the number of vehicle users is growing tremendously, wasting a significant amount of time and fuel while searching for an available parking space. This work highlights the optimum utilization of parking slots without the physical intervention of humans by making use of an IoT-integrated embedded system. This study aimed to create a mobile application for car parking that uses NodeMCU as the Microcontroller, which is further integrated with Radio-Frequency Identification (RFID) and the Internet of Things (IoT) to detect available parking slots, saving people’s time. When combined with an interactive mobile application, this technology provides an efficient solution by highlighting the availability and occupancy of parking spaces as green and red, respectively. It contributes to enhancing the quality of life of people living in congested metropolitan cities by digitizing the conventional parking system.
Keywords: Internet of Things; Radio-Frequency Identification; FASTag; Parking premises; Car Parking System